Antecedents of Career Growth: An Empirical Study in Higher Education Institutions - Wijaya, Lianna; Sriwidadi, Teguh; Samuel, Sylvia (Fakultas Ekonomi dan Bisnis, Telkom University., 2025)
Today's businesses place a paramount importance on the performance of their employees due to its direct correlation with growth and enhanced revenues. The primary objective of this research endeavor is to ascertain the impact of employee satisfaction, employee benefits, and employee learning on career growth and employee performance. A sample consisting of 400 individuals employed in the Higher Education Institutions of Indonesia served as the focal point of this study. The participants, selected through purposive sampling, were provided with self-reporting questionnaires to gather essential data. To evaluate the hypothesized relationships, the researchers employed structural equation modeling analysis utilizing AMOS 26. The findings of this study revealed that employee performance and career growth within Indonesia's higher education institutions were significantly influenced by employee learning, employee benefits, and employee satisfaction. Furthermore, employee performance was shown to have a substantial and positive effect on career growth. These findings contribute valuable insight and offer practical guidance for managerial decision-making. The theoretical and practical implications of these findings can lay a strong foundation for future research endeavors aimed at exploring career growth. It is recommended that the management of higher education institutions prioritize the career growth of their employees.